Finite element modeling of silver electrodeposition for evaluation of thickness distribution on complex geometries. (15th January 2016) - Belov, Ilja; Zanella, Caterina; Edström, Curt; Leisner, Peter
Abstract: The paper reveals benefits of multi-disciplinary computer simulation and parametric studies in the design of silver plating process for improved coating distribution. A finite element model of direct current silver plating is experimentally validated for an Assaf panel without agitation. The model combines tertiary current distribution with Butler–Volmer electrode kinetics and computational fluid dynamics at a very low flow-rate. The effect of charge transfer coefficients on the throwing power of the process is quantified for the studied geometry, and variation of cathodic current density and exchange current density is investigated. A simpler model based on secondary current distribution is employed to quantify the effect of electrolyte conductivity on the throwing power of the process. A model combining tertiary current distribution and computational fluid dynamics has been developed and experimentally validated for simulation of complex telecom component electroplating in agitated electrolyte. The effect of current density on the process throwing power is quantified. Recommendations regarding modeling methodology and the effect of electrochemical and process parameters on the thickness distribution have been developed. Graphical abstract: Highlights: Design guidelines for silver electrodeposition are developed using numerical modeling. Throwing power (TP) is sensitive to cathodic charge transfer coefficient (αc ). TP is less sensitive to conductivity and anodic charge transfer coefficient (αa ). αc and αa determined at actual plating conditions represent critical model inputs.